A new species of Campanula (Campanulaceae) from Turkey - Mutlu, Birol; Karakuş, Şükrü (Phytotaxa, 2015)
Campanula malatyaensis Mutlu & Karakuş is described as a new species from the Malatya province (Eastern Turkey). The new species belongs to section Tracheliopsis (Buser) Damboldt and morphologically resembles C. myritifolia Boiss. & Heldr. and C. fruticulosa (Schwarz & Davis) Damboldt. Morphological differences between C. malatyaensis and these taxa are discussed. This study presents SEM images (pollen, seed, corolla hair, and stylus hairs), photographs (type specimen, habitat, flowering specimens, and fruiting specimens), and conservation status of the new species.